Theoretical aspects of computing - ICTAC 2008 5th International Colloquium, Istanbul, Turkey, September 1-3, 2008 : proceedings - ICTAC (Colóquio) (Lecture notes in computer science ;)
This book constitutes the refereed proceedings of the 5th International Colloquium on Theoretical Aspects of Computing, ICTAC 2008 held in Istanbul, Turkey in September 2008. The 27 revised full papers were carefully reviewed and selected from over 70 submissions. The aim of the colloquium is to bring together practitioners and researchers from academia, industry and government to present research results, and exchange experience, ideas, and solutions for their problems in theoretical aspects of computing such as automata theory and formal languages, principles and semantics of programming languages, software architectures and their description languages, software specification, refinement, and verification, model checking and theorem proving, real-time, embedded and hybrid systems, theory of parallel, distributed, and internet-based (grid) computing, simulation and modeling, and service-oriented development. Using design patterns in formal methods: an event-B approach -- A unified approach to abstract interpretation, formal verification and testing of C/C++ modules -- The three platonic models of divergence-strict CSP -- Monotonic abstraction in action -- Non-interleaving semantics with causality for nondeterministic dataflow -- Symbolic reachability for process algebras with recursive data types -- Inclusion test algorithms for one-unambiguous regular expressions -- Refinement of Kripke models for dynamics -- Tomorrow and all our yesterdays: MTL satisfiability over the integers -- A theory of pointers for the UTP -- Recasting constraint automata into Büchi automata -- A complete realisability semantics for intersection types and arbitrary expansion variables -- Towards efficient verification of systems with dynamic process creation -- An observational model for transactional calculus of services orchestration -- Everything is PSPACE-complete in interaction systems -- A new approach for the construction of multiway decision graphs -- Congruence results of scope equivalence for a graph rewriting model of concurrent programs -- Guided test generation from CSP models -- Relaxing goodness is still good -- benchmarking model- and satisfiability-checking on bi-infinite time -- Formal analysis of workflows using UML 2.0 activities and graph transformation systems -- Testing concurrent objects with application-specific schedulers -- A theory of bounded fair scheduling -- Fair exchange is incomparable to consensus -- Automatic generation of CSP || B skeletons from xUML models -- Bounded model checking for partial Kripke structures -- Verification of linear duration invariants by model checking CTL properties -- Exact response time scheduling analysis of accumulatively monotonic multiframe real time tasks -- Endomorphisms for non-trivial non-linear loop invariant generation -- Instantiation for parameterised boolean equation systems.